2004
DOI: 10.1086/381405
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Variation of mtDNA Hypervariable Region 1 Suggests That Eastern and Western Pygmies Diverged before the Bantu Expansion

Abstract: The Eastern Pygmies from Zaire and Western Pygmies from Cameroon, Congo, and the Central African Republic represent the two principal groups of African Pygmies. In the "recent divergence" hypothesis in which Western Pygmies are thought to be the result of hybridization between the ancestors of Eastern Pygmies and Bantu farmers who penetrated the equatorial belt and came into contact with Pygmies around 2-3 kiloyears ago. On the basis of recent archaeological research in the tropical rain forest, we propose a "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
37
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 41 publications
9
37
0
Order By: Relevance
“…Furthermore resequencing 24 independent noncoding regions across the genome, Patin et al (2009) inferred the separation time between pygmy huntergatherers and African farmers to be 60000 years BP and the separation between the western and the eastern groups of pygmy as 20000 years BP. As for the latter, elsewhere, the separation time has been estimated at 18000 years BP based on mt-DNA analysis (Destro-Bisol et al, 2004). This genetic information indicates that the divergence between pygmy groups and other African groups was 70000-60000 years BP and the divergence of two Pygmy groups 20000-18000 years BP.…”
Section: The Paleolithic Foraging Lifestyle In the African Tropical Rmentioning
confidence: 98%
“…Furthermore resequencing 24 independent noncoding regions across the genome, Patin et al (2009) inferred the separation time between pygmy huntergatherers and African farmers to be 60000 years BP and the separation between the western and the eastern groups of pygmy as 20000 years BP. As for the latter, elsewhere, the separation time has been estimated at 18000 years BP based on mt-DNA analysis (Destro-Bisol et al, 2004). This genetic information indicates that the divergence between pygmy groups and other African groups was 70000-60000 years BP and the divergence of two Pygmy groups 20000-18000 years BP.…”
Section: The Paleolithic Foraging Lifestyle In the African Tropical Rmentioning
confidence: 98%
“…The analysis also shows that the Mbuti pygmies cluster with the SAK at higher K values (K = 7), which could be due to either common ancestry or more recent gene flow. In addition, recent work on mtDNA, NRY, and autosomal data estimated the TMRCA of the pygmy and agricultural populations to be approximately 70-60 kya and the TMRCA of western and eastern pygmies to be approximately 20 kya (73,102,103). The findings of Tishkoff et al (1) raise the possibility that the pygmy populations, who have lost their indigenous language, once spoke some form of proto-Khoesan with click consonants.…”
Section: Contemporary African Genetic and Linguistic Variationmentioning
confidence: 99%
“…However, peopling processes and migration dynamics remain poorly resolved in Africa, especially in CA. Patterns of mtDNA variation in AGR and PHG populations have been investigated in studies focusing on the control region [usually the hypervariable segment I (HVS-I)] and a few coding sites (14,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). A number of mtDNA haplogroups (Hgs) have been identified as possible genetic footprints of Bantu expansions.…”
mentioning
confidence: 99%
“…These Hgs include L0a (21,24,29), L1c (23,32), L2a (29,30), L3b (26), and L3e (27,28). Studies of small numbers of eastern Mbuti PHG, in which only HVS-I was investigated (14), have suggested that the mtDNA gene pool of eastern Pygmies differs substantially from that of western PHG, who display genetic similarities to neighboring farming populations (30,33,34). However, the actual origins of the PHG and AGR populations and their interactions in space and time remain unclear because of the small samples sizes and limited number of directly sampled populations from CA and the low molecular resolution achieved with HVS-I and a few RFLP markers only.…”
mentioning
confidence: 99%